Intramuscular vaccination targeting mucosal tumor draining lymph node enhances integrins-mediated CD8+ T cell infiltration to control mucosal tumor growth. (3rd August 2018) - Qiu, Jin; Peng, Shiwen; Yang, Andrew; Ma, Ying; Han, Liping; Cheng, Max A.; Farmer, Emily; Hung, Chien-Fu; Wu, T.-C.
ABSTRACT: Purpose : Mucosal immunization is suggested to be crucial for controlling tumors in the mucosal region; however, therapeutic DNA vaccination with electroporation in various mucosal sites has yet to become clinically adaptable. Since tumor-draining lymph nodes (tdLNs) have been suggested as immune-educated sites that can be utilized to mount a potent antitumor immune response, we examined whether intramuscular DNA vaccination with electroporation at sites that target the mucosal tdLNs could elicit mucosal immune response to restrict tumor growth. Experimental Design : The efficacy and mechanism of intramuscular administration of a therapeutic DNA vaccine with electroporation at different sites was examined by lymphocyte analysis, tumor growth, mouse survival, as well as integrin expression, in mice bearing orthotopic HPV16 E6/E7+ syngeneic TC-1 tumors in various mucosal areas. Results : While provoking comparable systemic CD8+ T cell responses, intramuscular hind leg vaccination generated stronger responses in cervicovaginal-draining LNs to control cervicovaginal tumors, whereas intramuscular front leg vaccination generated stronger responses in oral-draining LNs to control buccal tumors. Surgical removal of tdLNs abolished the antitumor effects of therapeutic vaccination. Mucosal-tdLN-targeted intramuscular vaccination induced the expression of mucosal-homing integrins LPAM-1 and CD49a by tumor-specific CD8+ T cells in the tdLNs. Inhibition of these integrins abolished the therapeutic effects of vaccination and the infiltration of tumor-specific CD8+ T cells into mucosal tumors. Conclusions : Our findings demonstrate that tumor draining lymph nodes targeted intramuscular immunization can effectively control mucosal tumors, which represents a readily adaptable strategy for treating mucosal cancers in humans.